2014
DOI: 10.1039/c4cc03435j
|View full text |Cite
|
Sign up to set email alerts
|

The first structural and spectroscopic characterisation of a ring-opened form of a 2H-naphtho[1,2-b]pyran: a novel photomerocyanine

Abstract: Heating 4-methoxy-1-naphthol with a 1,1-diarylprop-2-yn-1-ol gave the 2,2-diaryl-6-methoxy-2H-naphtho[1,2-b]pyran together with the novel merocyanine, (E)-2-[3',3'-bis(aryl)allylidene]-4-methoxynaphthalen-1(2H)-one. Brief UV-irradiation of the pyran favoured the formation of the (Z)-merocyanine with longer irradiation and/or acidic conditions favouring the (E)-isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Functionalized naphthalene derivatives such as naphthalenones are prevalent in natural products, optical/electronic materials, and pharmaceuticals. , Due to their importance, several synthetic protocols for the preparation of naphthalenone derivatives have been developed . While these literature methods are generally efficient and reliable, new methods starting from easily accessible substrates and accomplished through short and simple synthetic procedures with improved atom-economy are still highly desirable.…”
mentioning
confidence: 99%
“…Functionalized naphthalene derivatives such as naphthalenones are prevalent in natural products, optical/electronic materials, and pharmaceuticals. , Due to their importance, several synthetic protocols for the preparation of naphthalenone derivatives have been developed . While these literature methods are generally efficient and reliable, new methods starting from easily accessible substrates and accomplished through short and simple synthetic procedures with improved atom-economy are still highly desirable.…”
mentioning
confidence: 99%
“…This observation may simply be due to the kinetics of fading of these particular dyes. However, it has also been reported that certain naphthopyran‐based photochromic dyes may form two different stable, coloured isomers on irradiation: the major component, a short‐lived, strongly coloured species, which is the transoid‐cis isomer, and the minor component, a long‐lived, paler‐coloured transoid‐trans isomer .…”
Section: Resultsmentioning
confidence: 99%
“…The following benzochromene (naphthopyran) substrates used in this study were prepared according to literature procedures and possessed physical and spectroscopic properties that were in excellent agreement with those previously reported in the literature for their preparation: 3,3-bis­(4-methoxyphenyl)-3 H -benzo­[ f ]­chromene 21 ; 4-(3,3-bis­(4-methoxyphenyl)-3 H -benzo­[ f ]­chromen-6-yl)­morpholine 31 ; 3-(4-methoxyphenyl)-3-(thiophen-2-yl)-3 H -benzo­[ f ]­chromene 33 ; 2,2,11,11-tetrakis­(4-methoxyphenyl)-2,11-dihydrobenzo­[ f ]­pyrano­[3,2- h ]­chromene 37 ; 2,2,8,8-tetrakis­(4-methoxyphenyl)-2,8-dihydrochromeno­[6,5- f ]­chromene 39 ; 6-methoxy-2,2-bis­(4-methoxyphenyl)-2 H -benzo­[ h ]­chromene 45 ; 6-methoxy-2,2-bis­(4-methoxyphenyl)-4-( p -tolyl)-2 H -benzo­[ h ]­chromene 47 ; (6,6-bis­(4-methoxyphenyl)-6 H -benzo­[ h ]­furo­[3,2- f ]­chromen-3-yl)­(phenyl)­methanone 49 ; (6,6-bis­(4-methoxyphenyl)-4-( p -tolyl)-6 H -benzo­[ h ]­furo­[3,2- f ]­chromen-3-yl)­(phenyl)­methanone 51 ; and 8-bromo-3,3-bis­(4-methoxyphenyl)-3 H -benzo­[ f ]­chromene 53 …”
Section: Methodsmentioning
confidence: 99%
“…13 C{ 1 H} NMR spectra, mass spectral data for compounds22,29,30,32,34, 35,36,38,40,41,42, 46, 48, 50, 52, 55, and 56; selected 2D NMR spectra for compound 40 (PDF)…”
mentioning
confidence: 99%